PERAN PEMERINTAH KELURAHAN KADOLOMOKO DALAM UPAYA PENGENTASAN KEMISKINAN EKSTRIM DI KOTA BAUBAU - Mawar Melati; Farid Yusuf Nur Achmad; Junaid Gazalin (Journal Publicuho, 2025)
This study aims to analyse the role of the Kadolomoko Village Government in the effort to eradicate extreme poverty in Baubau City. Extreme poverty remains a major issue despite the implementation of various policies. The research method used is a qualitative approach with a case study, involving interviews with village government officials, community leaders, and beneficiaries of poverty alleviation programs. The results of the study show that although there are positive impacts from economic empowerment programs and social assistance distribution, significant challenges remain, such as data inaccuracy, limited resources, and poor coordination between related institutions. The study concludes that to improve policy effectiveness, improvements in the data system, more comprehensive entrepreneurship training, and better coordination between institutions are needed. Strengthening the budget and village officials' capacity also plays a key role in accelerating extreme poverty alleviation.